Soil depth and physicochemical properties influence microbial dynamics in the rhizosphere of two peruvian superfood trees, cherimoya and lucuma, as shown by PacBio-HiFi sequencing - Estrada Cañari, Richard; Porras Valencia, Angie Tatiana; Romero Avila, Yolanda Madelein; Pérez Porras, Wendy Elizabeth; Vilcara Cárdenas, Edgardo Arturo; Cruz Luis, Juancarlos Alejandro; Arbizu Berrocal, Carlos Irvin (Nature Publishing Group, 2024)
The characterization of soil microbial communities at different depths is essential to understand their impact on nutrient availability, soil fertility, plant growth and stress tolerance. We analyzed the microbial community at three depths (3 cm, 12 cm, and 30 cm) in the native fruit trees Annona cherimola (cherimoya) and Pouteria lucuma (lucuma), which provide fruits in vitamins, minerals, and antioxidants. We used PacBio-HiFi, a long-read high-throughput sequencing to explore the composition, diversity and putative functionality of rhizosphere bacterial communities at different soil depths. Bacterial diversity, encompassing various phyla, families, and genera, changed with depth. Notable differences were observed in the alpha diversity indices, especially the Shannon index. Beta diversity also varied based on plant type and depth. In cherimoya soils, positive correlations with Total Organic Carbon (TOC) and Cation Exchange Capacity (CEC) were observed, but negative ones with certain cations. In lucuma soils, indices like the Shannon index exhibited negative correlations with several metals and specific soil properties. We proposed that differences between the plant rhizosphere environments may explain the variance in their microbial diversity. This study provides insights into the microbial communities present at different soil depths, highlighting the prevalence of decomposer bacteria. Further research is necessary to elucidate their specific metabolic features and overall impact on crop growth and quality.